MEASURES TO REDUCE THE DEFECTIVENESS OF AVIATION PRODUCTS AND ASSESSMENT OF THE EFFECTIVENESS OF ITS IMPLEMENTATION - L. V. Orlova; P. V. Zobov (Вестник университета)
The article considers the problems of reducing the quality of aviation products, leading to the loss of competitiveness of finished products and an increase in cost price. In the course of the study, the authors analysed the reasons for the appearance of defective products at an aviation manufacturing enterprise. Based on the information received using modern data processing methods, the paper determines the main weaknesses of the considered technological stage of aviation products. Having studied modern international quality standards in the field of aviation construction, the authors proposed measures that would reduce the number of defective products and increase the reliability and competitiveness of finished products. The article presents separately the model for evaluating the effectiveness of measures to reduce the defectiveness of aviation products. The paper carries out assessment of the proposed tactical measures to reduce the level of defective products, which will increase the economic performance of production activities in certain areas of production.